Intraparenchymal NGF Infusions Rescue Degenerating Cholinergic Neurons - Mark H. Tuszynski M.d., Ph.D. (Cell Transplantation, 2000)
Nerve growth factor (NGF) exerts both trophic (cell survival) and tropic (axonal growth-promoting) effects on several neuronal populations. In particular, its robust ability to prevent lesion-induced and spontaneous age-related basal forebrain cholinergic neuronal degeneration, and to promote mnemonic recovery, has suggested its potential use as a therapeutic agent in Alzheimer's disease. When infused intracerebroventricularly, however, NGF is associated with several adverse effects that make this delivery route impractical. The present study examined whether intraparenchymal infusions of NGF adjacent to cholinergic neuronal soma are an effective and well-tolerated means of providing NGF to degenerating cholinergic neurons. Cholinergic neuronal rescue together with axonal sprouting responses and local tissue damage in the brain were assessed in adult rats that underwent complete unilateral fornix transections, followed by intraparenchymal infusions of recombinant human NGF for a 2-week period. Intraparenchymal NGF infusions prevented the degeneration of 94.7 ± 6.6% of basal forebrain cholinergic neurons compared to 21.7 ± 2.6% in vehicle-infused animals (p < 0.0001). Cholinergic axons sprouted toward the intraparenchymal NGF source in an apparent gradient-dependent manner. Glial responses to intraparenchymal infusions were minimal, and no apparent toxic effects of the infusions were observed. Thus, when infused intraparenchymally, NGF rescues basal forebrain cholinergic neurons, alters the topography of axonal sprouting responses, and does not induce adverse affects over a 2-week infusion period. Intraparenchymal NGF delivery merits further study at longer term time points as a means of treating the cholinergic component of neuronal loss in Alzheimer's disease.